POLÍTICAS DE ALFABETIZAÇÃO E EDUCAÇÃO DE JOVENS E ADULTOS EM MOÇAMBIQUE: uma análise sobre a concepção dos programas de EJA na Província de Nampula - Felix Matias (2021)
This study aims to analyze the design of youth and Adult Education Programs in Mozambique, particularly in Nampula Province, from national independence to the present day (1975 to 2020). We seek to understand the main ideas that guide the educational processes of the EJA modality in the country, especially with regard to the training perspective conceived; the milestones that characterize the trajectory of school education in Mozambique, and also the reflection on policies aimed at educating women; the role of civil society organizations in the design and implementation of education policies in Mozambique and their impacts. The methodological approach used for this study has a qualitative approach, and is characterized as descriptive, whose data source is bibliographic and documental analysis. Discussions were conducted based on the content analysis technique. The study concluded that from national independence to the present day, Mozambique has been showing a certain commitment in the design of EJA policies, because of this, there are several programs designed and implemented in local communities. The training perspective that dominates educational processes in the country today is of an economistic/neoliberal nature. This is evident from the principles and the general vision that guide education, where discourses from the millennium goals, sustainable development, are evident, given the internationalization of public education policies, with the presence of international organizations. It also concludes that the country faces several challenges in this area, characterized by limited resources, in a context in which human dignity is sought through education. KEYWORDS: Youth and Adult Education. Mozambique. Public Education Policies. Youth and Adult Literacy Programs. Impact of EJA Policies.